2015
DOI: 10.1080/19475705.2015.1084540
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hurricane wind damage by claim payout based on Hurricane Ike in Texas

Abstract: The increasing occurrence of natural disasters and their related damage have led to a growing demand for models that predict financial loss. Although considerable research on the financial losses related to natural disasters has found significant predictors, there has been a lack of comprehensive study that addresses the relationship among vulnerabilities, natural disasters, and the economic losses of individual buildings. This study identifies the vulnerability indicators for hurricanes to establish a metric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Among the natural hazards, this study found that the occurrence of flooding was proportional to the increase in third-party losses in bridge construction, which is consistent with the findings of previous studies that revealed that the elements of flooding are also key risk factors in construction projects [44]. In addition, as Kim et al [49] contended, the results of this study also indicate that the size of a construction project affects the potential loss. This study classified the size of a construction project into two different elements, the construction duration and rank of the construction company and verified that the rank of the company is the more significant factor of the two.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Among the natural hazards, this study found that the occurrence of flooding was proportional to the increase in third-party losses in bridge construction, which is consistent with the findings of previous studies that revealed that the elements of flooding are also key risk factors in construction projects [44]. In addition, as Kim et al [49] contended, the results of this study also indicate that the size of a construction project affects the potential loss. This study classified the size of a construction project into two different elements, the construction duration and rank of the construction company and verified that the rank of the company is the more significant factor of the two.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…The total value of the property is also statistically significant with windstorm damages. Kim et al (2016) denoted that the total value of the property has a negative relationship with the windstorm damage, as the total value of the property increases as the windstorm damages decreases. He also found that the value is not only a critical indicator, but also has the most dominant impact on the damage among the significant variables (Kim et al 2016).…”
Section: Line Of Business (Lob) and Tsimentioning
confidence: 99%
“…On the other hand, the reverse relationship is established for vulnerability. For instance, an old building is more prone to windstorms than a new building with a lower building value (Highfield et al 2010;Kim et al 2016).…”
Section: Line Of Business (Lob) and Tsimentioning
confidence: 99%
See 1 more Smart Citation
“…Most damage occurred in Gyeongnam and Busan, which are located on the right side of the typhoon path. The cause for this is that the typhoon landed on the coast of Gyeongnam, causing direct damage to the area and, in particular, to the area to the right side of the typhoon path due to the extremely strong winds and heavy rainfall [21]. In the right-sided area of the expected path of the typhoon, more efforts are needed to mitigate typhoon damage.…”
Section: Discussionmentioning
confidence: 99%